Impact of Co-Worker Ostracism on Organizational Citizenship Behavior Through Employee Self-Identity: The Moderating Role of Ethical Leadership - Zhang L; Liu Z; Li X (Psychology Research and Behavior Management, 2023)
Lianying Zhang, Ziqing Liu, Xiaocan Li College of Management and Economics, Tianjin University, Tianjin, People’s Republic of ChinaCorrespondence: Ziqing Liu, College of Management and Economics, Tianjin University, 92 Weijin Road, Nankai District, Tianjin, 300072, People’s Republic of China, Tel +86 16622808037, Email liuzq0128@163.comPurpose: Positive interpersonal interactions are indispensable for employees to engage in organizational citizenship behavior (OCB) that benefits teamwork; however, co-worker ostracism triggers interpersonal isolation, inhibiting OCB. This research aims to leverage the intervention of ethical leadership in the ostracism–OCB relationship to moderate the harmful ostracism and promote ostracized employees’ OCB through employee self-identity.Methods: This research chose 122 MBA to participate in Study 1’s scenario experiment to verify the causality between variables. Study 2 used 295 valid questionnaires from full-time employees to generalize the experimental results to field settings and compensate for external validity. Two studies used Hayes’s conditional process model to test the conditional direct and indirect relationships.Findings: This research revealed that high levels of ethical leadership effectively transitioned the harmful ostracism and promoted ostracized employees’ OCB by satisfying ostracized employees’ needs for identity recognition. Accordingly, the direct and indirect effects of co-worker ostracism on OCB through employee self-identity would be positive at high levels of ethical leadership, but negative at low levels.Originality: This research first introduces an identity perspective on ethical leadership in moderating the ostracism–OCB relationship. Based on the social identity theory of leadership, this research fills the gap in ostracism and OCB research calling for leadership interventions. It extends a novel insight into inspiring ostracized employees’ participation in OCB through employee self-identity.Practical Implications: This research provides the managerial applications of ethical leadership for China organizations to reduce inadvertent inactions, accept employees’ identities, and value interpersonal communication for effectively transitioning harmful ostracism.Keywords: ethical leadership, co-worker ostracism, organizational citizenship behavior, individual identity, relational identity, collective identity